2019
DOI: 10.1001/jamanetworkopen.2019.14078
|View full text |Cite
|
Sign up to set email alerts
|

Association of Punitive and Reporting State Policies Related to Substance Use in Pregnancy With Rates of Neonatal Abstinence Syndrome

Abstract: This cross-sectional study examines the association of state-level punitive or reporting policies related to substance use during pregnancy with rates of neonatal abstinence syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 36 publications
(82 reference statements)
4
63
0
Order By: Relevance
“…Health policy related to mandatory reporting laws for pregnant and postpartum women with OUD should be evidence‐based and therapeutic in nature. States with punitive reporting policies have higher rates of NAS, possibly the consequence of women avoiding care out of fear of being reported 28 …”
Section: Discussionmentioning
confidence: 99%
“…Health policy related to mandatory reporting laws for pregnant and postpartum women with OUD should be evidence‐based and therapeutic in nature. States with punitive reporting policies have higher rates of NAS, possibly the consequence of women avoiding care out of fear of being reported 28 …”
Section: Discussionmentioning
confidence: 99%
“…However, as the recent analysis of state policy and NAS rates in the study by Faherty et al 1 suggested, punitive approaches are counterproductive and instead are associated with higher rates of NAS.…”
mentioning
confidence: 99%
“…A second barrier includes the punitive consequences stemming from state laws regarding prenatal substance use, which can result in patients not wanting to disclose and physicians not wanting to learn about their patients' behaviors. [53][54][55] Hence, in addition to patients' previous fears about stigmatization because of use, disclosure could now pose a legal risk. 56 An example of a punitive policy includes treating substance use during pregnancy as child abuse or neglect.…”
Section: Barriers To Early Identification By Screeningmentioning
confidence: 99%